Kebijakan Pendidikan Pemerintah Indonesia Era Orde Baru Serta Pengaruhnya terhadap Pendidikan Islam di Indonesia - Sasmita Hasdiana; Nurazizah Alamsyah; Kasful Anwar US; Sya'roni Sya'roni (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This paper discusses the Indonesian government's education policy in the New Order era and its influence on Islamic education in Indonesia. This paper aims to find out how education policy in Indonesia in the New Order era was and its influence on Islamic education in Indonesia. The New Order provided a new style for Islamic religious education policy, because the influence of communism shifted towards strengthening Pancasila through a sustainable national development plan. Education is the main pillar of the founding of a nation. Education is an effort to design the future of humans as a generation that will advance a nation. The concept of education applied in Indonesia has never been separated from political elements and government policies. Education during the New Order era was a short-term education system or, in other words, centralization, making the quality of Indonesian education increasingly worse. Thus, education during the New Order era was not aimed at improving people's standard of living, let alone improving Indonesia's human resources, but prioritized political orientation so that all people always obeyed every government policy. Education is a link in the process of guiding and cultivating good human abilities. Apart from that, education is an introduction to humanity to a greater or higher civilization based on the balance of human life, the environment and the Creator. Education is a field which is related to human life. The general aim of Islamic education is to make the personality of every believer have advanced thinking, ready to legalize every truth of his knowledge, and expert in implementing the knowledge he has. The goals of Islamic education can be realized if it is carried out according to the correct basics, namely the Koran and Hadith. One of these government regulations is regulations. Regarding the nine-year compulsory education program, namely elementary school and junior high school or equivalent. Therefore, Islamic education has existed since the Old Order era until the Reformation era, where the quality of education has increasingly improved and experienced good changes.